Exposures to great Chinese Famine during embryo, foetal or infant stages link differently with risks of cardiovascular diseases in late middle age - Xiuwen Zhou; Yumeng Zhang; Qiutong Zheng; Yi Ding; Daiyi Zhang; Jianhong Pu; Zhice Xu (Journal of Nutritional Science)
Perinatal malnutrition is a critical cause of diseases in offspring. Based on the different rates of organ development, we hypothesised that malnutrition at varying early life stages would have a differential impact on cardiovascular disease in middle-aged and older adults. This study sought to assess the long-term impact of exposure to the 1959–1961 Great Chinese Famine (GCF) during early developmental periods on risks of cardiovascular diseases in the late middle-aged offspring. A total 6, 662 individuals, born between 1958 and 1964, were divided into six groups according to the birth date. The generalised line model was used to control age and estimate differences with 95% confidence interval (CI) in blood pressure. Binary logistic regression was applied to evaluate the association between famine exposure and cardiovascular diseases. Compared to the unexposed late middle-aged persons, blood pressure was elevated in the entire gestation exposure group, regardless of postnatal exposure to GCF. Increased blood pressure was also found in the female offspring exposed to GCF during early and middle gestation. The early-childhood exposure was associated with the risk of bradycardia in the offspring. The risks of vertebral artery atherosclerosis were elevated in GCF famine-exposed groups except first trimester exposed group. The chronic influence of GCF in early life periods was specific to the developmental timing window, sexesand organs, suggesting an essential role of interactions among multiple factors and prenatal malnutrition in developmentally “programming” cardiovascular diseases.